Psathyrella tintinnabula sp. nov. (Psathyrellaceae, Agaricales), a new species from southwest China - Yan, Jun-Qing; Ge, Yupeng; Hu, Dianming; Zhou, Jianping; Huo, Guang-Hua (Phytotaxa, 2019)
Psathyrella tintinnabula is discovered in Yunnan Province of China, which is characterized by its small-sized basidiomata, bell-shape pileus, small-sized basidiospores and fusiform pleurocystidia with subacute apex. The studies of morphological characteristics and phylogenetic analyses showed that the new species is unique and evidently distinct from related species within the genus Psathyrella. Detailed description, color photos, illustrations and key to related species are presented.